Comparison of carbamazepine and lithium in treatment of bipolar disorder: a systematic review of randomized controlled trials. - Ceron-Litvoc, D; Soares, BG; Geddes, J; Litvoc, J; de Lima, MS (2009)
OBJECTIVES: To review data from randomized controlled trials (RCTs) assessing the comparative efficacy of carbamazepine and lithium in treatment of acute manic and maintenance phase of bipolar disorder (BD). DESIGN: RCTs were identified through a search strategy that included: electronic databases, reference cross-checking, hand search of non-indexed publications, and book chapters on the treatment of BD comparing carbamazepine with lithium. Outcomes investigated were antimanic effect, trial withdrawal, relapse, hospitalization, need for rescue medication, and presence of adverse effects. Selection of studies and data analysis were performed independently by authors. Whenever possible, data from trials were combined through meta-analyses. Relative risks (RR) were estimated for dichotomous data. RESULTS: In acute mania, carbamazepine was similar to lithium on the following outcomes: trial withdrawal due to adverse effects, number of participants with at least one adverse effect, improvement in the Clinical Global Impression (CGI). In acute mania, carbamazepine was associated with fewer trial withdrawals. In maintenance treatment, carbamazepine was similar to lithium in relapses and hospitalization, but there were fewer trial withdrawals due to adverse effects on lithium. CONCLUSION: This review suggests that carbamazepine might be comparable to lithium in terms of efficacy and safety, and therefore a valuable option in the treatment of both manic and maintenance phases.